FAMILY FINANCIAL SOCIALIZATION AND GEN Z'S FINANCIAL BEHAVIOR: MEDIATING ROLE OF FINANCIAL SELF-EFFICACY : Sosialisasi Keuangan Keluarga dan Perilaku Keuangan Gen Z: Peran Mediasi Efikasi Diri Keuangan - Rachmaniar Myrianda Dwiputri; Hurriyyatun Kabbaro (Faculty of Social Science and Human Ecology, IPB University, 2025)
Generation Z often faces challenges in managing personal finances due to consumptive behavior and the convenience of digital transactions. This study investigates the influence of family financial socialization on the financial behavior of Generation Z, with financial self-efficacy serving as a mediating variable. A total of 418 college students born in 1997 or later (maximum age 28) participated in the study, which employed a quantitative approach and a convenience sampling technique—a non-probability method based on participant availability and willingness. Data were collected via an online survey and analyzed using structural equation modeling (SEM). The findings indicated that family financial socialization significantly and positively influenced financial behavior. Furthermore, financial self-efficacy was proven to partially mediate this relationship, suggesting that family influences were transmitted both directly and indirectly through the development of financial confidence. These results emphasize the critical role of parents as early financial educators and role models in fostering responsible financial habits. This study contributes to the literature by highlighting the mediating role of financial self-efficacy in the link between financial socialization and financial behavior among young adults.